The Protection of the Land Rights Guarantee in Indonesia from the Perspective of Human Rights for Social Justice - Joko Martono; Setyo Utomo; Purwanto Purwanto (Proceedings of AICS - Social Sciences, 2018)
Land is one component of human rights. However the real guarantee of the protection of land rights does not yet have a specific space in many international arenas, however the absence of discourse references does not cover the protection spaces that can still be found in many international human rights legal instruments. The formulation of the issues that will be discussed further in this paper as follows: How to Guarantee Protection of Land Rights in Indonesia from Human Rights Perspective. The purpose of writing is to build a strong discourse among civil society that can then be used as a reference by academics and government apparatus in encouraging the space of guarantee of the protection of land rights. In collecting accurate data and information, the authors used two data collection techniques, namely: literature study and limited group discussion. The conclusion of this paper is that transforming land rights to domestic legal relations is also a progressive action that must be done by state managers, as also described in the International Covenant on Economic, Social and Cultural Rights (1966). Efforts to progressive realization of land rights should be done consistently by the Government of Indonesia.Keywords:protection guarantee, land rights, social justice.